(untitled) (KYAMC Journal, 2023)
Background: Preeclampsia and eclampsia syndrome is one of the commonest medical disorders of females. The neonatal outcome is different from the normal pregnancy due to this disorder. It includes- stillbirth, low birth weight, asphyxia, and prematurity. Objective: The objective of the study was to determine the fetal outcomes in different groups of preeclampsia and eclampsia syndrome. Materials and Methods: This cross-sectional observational study was conducted in the Department of Pathology, (BIRDEM) General Hospital, Dhaka, from July 2019 to June 2021. The study comprised 138 clinically diagnosed preeclampsia and eclampsia syndrome cases from the Department of Gynecology & Obstetric of BIRDEM and DMCH. Out of 138 cases, there were 42 cases of mild preeclampsia (mild PE), 62 were of severe preeclampsia (severe PE), and 33 were eclampsia. Relevant data and pregnancy outcome (neonatal birth weight, maturity, Apgar score, and stillbirth), were observed and recorded in a predesigned data collection sheet and statistical analyses were carried out. Ethical practice was ensured in every step of the study. Results: Among 138 cases, the mean birth weight was (2.12±0.57) kg, which was observed in the mild preeclamptic group, and the mean birth weight was (1.52±0.47) kg found in the eclamptic group. A low Apgar score (score˂7) was mainly observed in the severe PE (77.8%) followed by (84.8%) in eclampsia group. More than half of the cases were revealed stillbirth (54.4%) as the neonatal outcome in eclampsia group. A statistically significant difference was found among three groups regarding pregnancy outcome (neonatal birth weight, maturity, stillbirth, etc.). Conclusion: Majority of the fetal complications were related to the severity and duration of the preeclampsia and eclampsia syndrome. KYAMC Journal Vol. 14, No. 01, April 2023: 39-42